3D frictional contact of graded magneto-electro-elastic film-substrate system under electromagnetic fields. (1st May 2023) - Sui, Yijin; Wang, Wenzhong; Zhang, Haibo; Liang, He
Highlights: The FRFs of multilayered magneto-electro-elastic (MEE) material are derived. Multiphysics-coupled contact of graded MEE film-substrate system is studied. Exponentially varying graded film with gradient index less than one is preferred. Less piezoelectric phase at surface presents larger magnetic potential output. Abstract: The 3D frictional contact model of graded magneto-electro-elastic (MEE) film-substrate system under electromagnetic fields is presented. The semi-analytical method (SAM) is used to solve this multi-physical contact problem. Firstly, the frequency response functions (FRFs) for every layer of MEE material subjected to unit mechanical, electric and magnetic loads are derived. Conjugate gradient method (CGM) is then employed to obtain contact responses with Discrete convolution-fast Fourier transformation (DC-FFT) speeding related calculations. Finally, multilayered model is used to approximate graded film with two types of grads, exponentially varying grad (EVG) and volume-fraction varying grad (FVG), the effects of the type and thickness of graded film and the friction coefficient are investigated. The results show that EVG film with gradient index less than one or FVG film with smaller volume fraction of piezoelectric phase at the surface are preferred for the MEE film-substrate systems.